Optimizing the role of tax auditor in attempt to achieve tax revenue target - Mawan Setianto; Hamidah Hamidah (Universitas Islam Indonesia, 2016)
This study aims to explain the role of Tax Auditor in KPP Madya Surabaya. This study uses a case study by collecting the data from Directorate General of Taxation official sources, either in KPP Madya Surabaya, Regional Office of Directorate General of Taxation East Java I, as well as the Directorate of Potency, Compliance, and Revenue. Researcher also conducted interviews with 12 informants consisting of Tax Auditor, Account Representative, Head of Office, as well as officials from the Directorate of Inspection and Billing. There are discrepancies between the expectations of stakeholders and what being understood/perceived and expected by the Tax Auditor in relation to the role that must be executed. This causes the Tax Auditor to experience a role ambiguity which disrupts the optimizing the implementation of the role. Things that still impede the implementation of the role of the Tax Auditor are: rejection of the Taxpayer; intervention both from inside and outside/difficult to implement the independence in appearance and independence in fact; both physically and psychologically threats; the unclear mutation policy; promotion criteria being implemented inconsistently; and databases that have not been accurate and reliable.